Model And Algorithm Super Resolution For Increase Effectively Digital Antenna Array - et. al., Sarmad Kadhim Dhiab, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The focus of this research paper is to model super resolution algorithm based system for enhanced digital antenna array propagation. In most of these areas, a large effort has been made by researchers and system manufacturers to develop sensors and transmission components that enable super-resolution digital antenna array. However, resolution is inherently limited. The resolution of a digital signal transmission based system characterizes the level of spatial detail at which it captures signals and – besides the contrast resolution – it is considered as a major quality indicator. This is obvious in digital signal transmission, where the super resolution algorithm is directly related to the acquisition of fine textures in a scene. In remote sensing as another prominent example, one is interested in measuring information on a planet surface over long distances, which requires super-resolution algorithm. The focus of this research lies in computational techniques that consider the pixel pitch as the limiting property for digital antenna array. Super resolution method has the objective to reconstruct digital array at finer array sampling from one or an entire sequence of under-sampled array and have been widely investigated in signal processing. This improvement of the array sampling is due to redundancies or complementary information encoded in low-resolution arrays. As the primary goal in this area lies in an enhancement of the digital array sampling, we use the super resolution technique. The research introduces novel multi-channel super-resolution algorithms that are applicable to various digital antenna array setups. The multi-channel super resolution algorithm exploits the existence of a set of modalities in contrast to conventional methods that consider only a single one with an outstanding accuracy of 96.89% for classification of all digital antenna arrays at the clock speed of 100 MHz with the size of each processing element is 108 microns on python platform.